Why is Normative Commitment Invalid? An Empirical Study on Principals of Public Elementary Schools - Kamaludin Kamaludin (Al Ibtida: Jurnal Pendidikan Guru MI, 2023)
The purpose of this study is to assess the construct validity of the principal's commitment to the proposed theory so that it can be seen that the observation variable can form a latent variable. The research approach used in this study uses a quantitative approach with a measurement model in the form of First Order Confirmatory Factor Analysis. The sample in this study amounted to 233 principals of State Elementary Schools. The location in this study is Brebes Regency, Central Java Province, Indonesia. The data analysis in this research is starting by developing a theoretical model, making a causal relationship path diagram, choosing an input matrix and getting a model estimate, assessing the identification of structural models, and assessing the criteria for Goodness of Fit. The research findings in this study are the dimensions of the principal's commitment measurement include affective, sustainability, and normative commitment, indicating that the normative dimension is invalid and insignificant in measuring the principal's commitment. This proves that commitment does not arise only because of concerns about the bad opinions of colleagues if the principal does not stay in school.